Women's perceptions of fertility assessment and counselling 6 years after attending a Fertility Assessment and Counselling clinic in Denmark. Issue 4 (5th October 2020) - Koert, E; Sylvest, R; Vittrup, I; Hvidman, H W; Birch Petersen, K; Boivin, J; Nyboe Andersen, A; Schmidt, L
Abstract: STUDY QUESTION: What are women's perceptions and experience of fertility assessment and counselling 6 years after attending a Fertility Assessment and Counselling (FAC) clinic in Denmark? SUMMARY ANSWER: Women viewed the personalized fertility knowledge and advice they received as important aids to decision-making and they felt the benefits outweighed the risks of receiving personalized fertility information. WHAT IS KNOWN ALREADY: Many young people wish to become parents in the future. However, research demonstrates there is a gap in women's and men's knowledge of fertility and suggests they may be making fertility decisions based on inaccurate information. Experts have called for the development of interventions to increase fertility awareness so that men and women can make informed fertility decisions and achieve their family-building goals. Since 2011, the FAC clinic in Copenhagen, Denmark has provided personalized fertility assessment and guidance based on clinical examination and evaluation of individual risk factors. Available qualitative research showed that attending the FAC clinic increased fertility awareness and knowledge and was experienced as a catalyst for change (e.g. starting to conceive, pursuing fertility treatment, ending a relationship) in women 1-year post-consultation. STUDY DESIGN, SIZE, DURATION: The study was a 6-year follow-up qualitative study of 24 women who attended the FAC clinic between January and June 2012. All women were interviewed during a 2-month period from February to March 2018 at Rigshospitalet, their home or office, in Copenhagen, Denmark. Interviews were held in English and ranged between 60 and 94 min (mean 73 min). PARTICIPANTS/MATERIALS, SETTING, METHODS: Invitations to participate in an interview-based follow-up study were sent to 141 women who attended the FAC clinic in 2012. In total, 95 women read the invitation, 35 confirmed interest in participating and 16 declined to participate. Twenty-five interviews were booked and 24 interviews held. Interviews followed a semi-structured format regarding reasons for attending the FAC clinic, if/how their needs were met, and perceptions of fertility assessment and counselling. Data were analysed using thematic analysis. MAIN RESULTS AND THE ROLE OF CHANCE: At the follow-up interview, women were on average 39.5 years old. Ten were currently single or dating and 14 were married/cohabiting. All were childless when they attended the FAC clinic. At the follow-up interview, 21 women were parents (14 women with one child; 6 with two children; 1 with three children) and the remaining three women intended to have children in the future. The most common reason for originally attending the FAC clinic was to determine how long they could delay childbearing. Most of the women now believed their needs for attending had been met. Those who were dissatisfied cited a desire for more exact ('concrete') information as to their remaining years of fertility, although acknowledged that this was likely not realistic. Women stated that they had felt reassured as to their fertility status after attending the FAC clinic whilst receiving the message that they could not delay childbearing 'too long'. Women viewed personalized fertility knowledge as an important aid to decision-making but cautioned about developing a false sense of security about their fertility and chance of conceiving in the future based on the results. Although women were generally satisfied with their experience, they wished for more time to discuss options and to receive additional guidance after their initial meeting at the FAC clinic. LIMITATIONS, REASONS FOR CAUTION: Participants were from a group of Danish women attending the FAC clinic and interviews were conducted in English, which means they are not representative of all reproductive-aged women. Nevertheless, the study group included a broad spectrum of women who achieved parenthood through different means (heterosexual/lesbian relationship, single parent with donor, co-parent) with various family sizes, and women who were currently childless. WIDER IMPLICATIONS OF THE FINDINGS: Our study provides support for an individualized approach to fertility education, assessment and counselling provided at a time when the information is relevant to the individual and their current fertility decision-making. The findings suggest that although satisfied with their visit to the FAC clinic, the women wished for more information and guidance after this visit, suggesting that the current intervention may need to be expanded or new interventions developed to meet these additional needs. STUDY FUNDING/COMPETING INTEREST(S): E.K. was funded by an ESHRE Travel/Training grant by ReproUnion, co-financed by the European Union, Interreg V OKS. J.B. reports that the risk evaluation form used at the Fertility Assessment Clinic was inspired by the Fertility Status Awareness Tool FertiSTAT that was developed at Cardiff University for self-assessment of reproductive risk. J.B. also reports personal fees from Merck KGaA, Merck AB, Theramex, Ferring Pharmaceuticals A/S and a research grant from Merck Serono Ltd outside the submitted work. A.N.A. has received personal fees from both Merck Pharmaceuticals and Ferring and grants from Roche Diagnostics outside the submitted work. The other authors report no conflicts of interest.